On Subclasses of Analytic Functions with respect to Symmetrical Points - Muhammad Arif; Khalida Inayat Noor; Rafiullah Khan (Abstract and Applied Analysis)
In our present investigation, motivated from Noor work, we define the class ℛks(b) of functions of bounded radius rotation of complex order b with respect to symmetrical points and learn some of its basic properties. We also apply this concept to define the class Hks(α,b,δ). We study some interesting results, including arc length, coefficient difference, and univalence sufficient condition for this class.